USE OF ARTHROSCOPY IN THE EARLY TREATMENT OF LARGE TIBIAL LUMPS - Tuxtayev Matyoqub Qushiyevich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. The purpose of the research work is to apply the modern method of treatment of fractures of large tibial bones and to demonstrate the reduction of complications after treatment. S right in years The frequency of articular fractures of proximal metaepiphysis of the tibia is constantly increasing, these fractures account for 10% of articular fractures in the locomotor system, 2% to 5% of total fractures, and 30% of leg injuries, which means that this problem is extremely urgent. This method was used in 37 patients, in all of whom positive and satisfactory results were obtained. The proposed method is highly effective and can be widely used in medicine.